PEMBINAAN REMAJA KARANG TARUNA DESA MEDALKRISNA MELALUI PELATIHAN PENGELASAN SMAW DI KECAMATAN BOJONGMANGU - Mashur, Teguh Abilah; Arrahim, Arrahim; Ramadhan, Fakhran (An-Nizam, 2024)
The problems faced by the youth organization of Medalkrisna village include activities held by the youth organization that have not yet increased the skills or skills of its members, there is no business opportunity that will be run as a source of activities and management of the youth organization. One of the welding methods is SMAW (Shield Metal Arc Welding) welding, which is welding using electric electrodes. The purpose of this activity is of course to increase knowledge and skills to youth coral cadets of Medalkrisna Village, Bojongmangu District, adding special skills in the form of welding expertise. The benefits of this training are of course providing knowledge and training welding skills which are certainly needed by youth youth to improve hard skills and soft skills so that they can be used for personal self-development and social benefits in society. Welding training is very much needed including entrepreneurship, industry and in projects. The success of this service activity has a good impact on helping the difficulties of youth organizations in the Medalkrisna Village area in an effort to increase their skills in the field of SMAW welding (Shield Metal Arc Welding).